Answer: x = 2
y = 2
Step-by-step explanation:
The given system of equations is expressed as
y = x²- 3x + 4- - - - - - - - - - - - -1
x + y = 4- - - - - - - - - - - -2
We would the method of substitution by substituting equation 1 into equation 2. It becomes
x + x²- 3x + 4 = 4- - - - - - - - - - -3
x² + x - 3x + 4 = 4
x² - 2x + 4 = 4
Subtracting 4 from the left hand side and the right hand side of the equation, it becomes
x² - 2x + 4 - 4 = 4 - 4
x² - 2x = 0
Adding 2x to the left hand side and the right hand side of the equation, it becomes
x² - 2x + 2x = 0 + 2x
x² = 2x
Dividing the left hand side and the right hand side of the equation by x, it becomes
x²/x = 2x/x
x = 2
Substituting x = 2 into equation 1, it becomes
y = 2²- 3 × 2 + 4
y = 4 - 6 + 4
y = 2